Dual Band to Wideband Pentagon-shaped Patch Antenna with Frequency Reconfigurability using EBGs - Raimi Dewan; M. K. A. Rahim; M. R. Hamid; M. F. M. Yusoff; H. A. Majid; B. A. F. Esmail (International Journal of Electrical and Computer Engineering (IJECE), 2018)
A dual band to wideband reconfigurable pentagon-shaped antenna with EBG unit cell is proposed. A minimal number of two EBG unit cell is deployed to realize frequency reconfigurable mechanism.  By varying the state of the EBG the antenna is capable to change its dual band operation to wideband alternately. There are three cases that have been analysed, first case is the EBG incorporated antenna with ideal and second is with the active EBG. Subsequently, the third cases is the fabricated ideal EBG incorporated antenna. The dual band operation is at 1.8 GHz and 5.2 GHz while the wide band from 1.6 GHz to 2.37 GHz (770 MHz). The proposed reconfigurable antenna is suitable to be implemented for LTE (1.6 GHz), Wi-Fi (5.2 GHz), WiMAX (2.3 GHz) and cognitive radio application.